The Transfer of HRM Policies and Practices in American Multinational Hotels in Saudi Arabia - Alkhaldi, Amal Hatem; Burgess, John; Connell, Julia (International Research Journal of Business Studies, 2014)
Global competition in the international business environment has pushed companies to achieve competitive advantage through mergers, acquisitions and through locating their subsidiaries in less developed counties for cost effectiveness. Consequently, the competitive pressure has increased the significance of human resource management (HRM) in multinational companies (MNCs), and MNCs have recognised the significance of the transfer HRM process across borders. This study examines the transfer of HRM policies and practices of US MNCs to their subsidiaries in Saudi Arabia. The aim of the study is to determine the extent to which US MNCs transfer HRM policies and practices from their Headquarters to their subsidiaries in Saudi Arabia; and identify the factors that facilitate and inhibit HRM transfer. The paper is based on an investigation of the interaction between home-country and host-country effects in determining HRM policies and practices in MNCs in the context of the Middle East. The study adopts a mixed methods approach of documentary analysis, focus group interviews of employees and in depth interviews of key informants in four subsidiaries of US owned international hotel chains located in Riyadh, Saudi Arabia.